Conditions - Zanbak, Keira (My University, 2020)
Conditions is a collection of written works by women, their experiences in life, and their thoughts and views on the world. It features six poems, two short stories, and an interview with author Adrienne Rich. The book is illustrated with imagery of mountains, hot weather, and desserts, settings that are often referenced in the stories. On a deeper level, a theme that runs through the book is that of rejection of traditional expectations of women and femininity. For this reason, motifs like flowers and the colour pink were avoided purposely. The typefaces Playfair Display and Crimson Text were chosen to match the overall feel of beauty that is communicated in this collection, as well as the elegance and quality of the written pieces. The layout was kept traditional to accommodate a wide variety of different types of work included in the collection; large headings and ample white space was used to separate each writing.
Presented in absentia on April 27, 2020 at "Student Research Day" at MacEwan University in Edmonton, Alberta. (Conference cancelled)
Keywords: typography; book design